2019
DOI: 10.1016/j.pmedr.2019.100839
|View full text |Cite
|
Sign up to set email alerts
|

Web-based intervention to promote weight-loss maintenance using an activity monitor: A randomized controlled trial

Abstract: The present study examined whether a web-based intervention could promote weight-loss maintenance, after weight loss. The study was a two-phase, 27-month, randomized controlled trial conducted in Ibaraki, Japan, from 2014 to 2017; 133 participants were recruited through local newspaper advertisements. The eligibility criteria were as follows: age of 40–64 years, body mass index of 25–40 kg/m2, and having at least one metabolic syndrome component. In phase 1, a 3-month, group-based weight-loss program was provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…Next, with smaller numbers, the study by Scott and colleagues [38] reported three MoAs and Wing and colleagues [44] reported only one. Four studies did not report any MoA (k = 4; 36%) [37,39,42,43].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…Next, with smaller numbers, the study by Scott and colleagues [38] reported three MoAs and Wing and colleagues [44] reported only one. Four studies did not report any MoA (k = 4; 36%) [37,39,42,43].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…The exception was the trial by Thomas and colleagues [39], in which the intervention group maintained an average weight loss of 10%, significantly greater than the comparative group. Physical activity outcomes were reported in six interventions, of these three reported no significant differences between groups [41][42][43], two observed a decrease in physical activity in the group receiving DBCI in comparison to those receiving personal contact [35,44], and one study found a small significant difference in which the intervention group was significantly more physically active than the control group [45,46].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations